2022
DOI: 10.1002/lno.12202
|View full text |Cite
|
Sign up to set email alerts
|

Identifying trait‐based tolerance to sediment dynamics during seedling establishment across eight mangrove species

Abstract: Mechanical disturbance from waves and sediment dynamics is a key bottleneck to mangrove seedling establishment. Yet, how species vary in tolerance to sediment dynamics has not been quantified. We identified how tolerance to sediment dynamics differs for three mangrove propagule traits: propagule size, successional stage, and type of embryo development. We selected eight mangrove species growing in south China that vary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
(91 reference statements)
0
12
0
1
Order By: Relevance
“…In this way, longer‐term models can incorporate annual seedling dynamics without the need to resolve hydrodynamics and morphological processes for the entire year. The resulting reduction in computational time can be invested in the consideration of other morphological and ecological processes relevant at these longer timescales, such as the influence of surface elevation and associated hydroperiod changes, competition for space and resources (Chen & Twilley, 1998; Clarke, 1995), or adaptive seedling growth in response to environmental forcing (Van Hespen et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, longer‐term models can incorporate annual seedling dynamics without the need to resolve hydrodynamics and morphological processes for the entire year. The resulting reduction in computational time can be invested in the consideration of other morphological and ecological processes relevant at these longer timescales, such as the influence of surface elevation and associated hydroperiod changes, competition for space and resources (Chen & Twilley, 1998; Clarke, 1995), or adaptive seedling growth in response to environmental forcing (Van Hespen et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These values are selected following previously reported Avicennia marina seedling characteristics from the Firth (Figures 3a–3c in Balke et al., 2015) and following Van Hespen et al. (2022). The initial shoot length was set equal to the propagule size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the sedimentation rate exceeds the rate of mangrove seedling growth, they can be buried as well. Recent experiment examined seedlings' accretion and erosion thresholds which showed that seedlings are likely to survival sediment accretion (10 out of 12 specimens) while, for some species, the seedlings can be negatively affected by sediment erosion [68]. Sediments can be brought to the mangrove region by massive flooding, upland erosion, and mud and debris flow.…”
Section: Coastal Sedimentation and Erosion Prevention Within Mangrovesmentioning
confidence: 99%
“…Those variables were also evaluated in studies with other mangrove species in controlled conditions (mesocosm experiments) (Balke et al, 2013;Gillis et al, 2019;Silva and Maia, 2019;van Hespen et al, 2022) and in field situations (Ewel and Baldwin, 2022;Sinsin et al, 2022;Sloey et al, 2022). Despite these studies, there are gaps in knowledge about the relationship between recruitment dynamics and seedling mortality.…”
mentioning
confidence: 99%